Using prequestions to enhance learning from reading passages: the roles of question type and structure building ability. Issue 9 (21st October 2019) - St. Hilaire, Kyle J.; Carpenter, Shana K.; Jennings, Janine M.
ABSTRACT: Answering questions before learning something ("prequestions") enhances learning. However, these benefits usually occur for information that was asked in the prequestions (i.e. prequestioned material), and not for non-prequestioned material. We reasoned that this narrow benefit may be due to the fact that studies typically use fairly simple prequestions that have a clear answer within one part of the learning material – isolative prequestions . We explored the effects of integrative prequestions that required participants to make connections across different parts of a reading passage. Experiment 1 showed the usual benefit of isolative prequestions on prequestioned but not on non-prequestioned material, but no benefit of integrative prequestions. However, in Experiment 2 when participants were given instructions to seek the answers while reading, integrative prequestions benefited learning of both prequestioned and non-prequestioned material. Individual differences in structure building positively predicted performance, but did not interact with the effects of prequestions.